Culturas juvenis na escola pública: contextos de uma instituição de ensino médio em Tucano-Ba - Santos, Magali Suzana (2019)
This academic study investigated "Youth cultures in the public school: contexts of a high school institution in Tucano-BA", taking as reference the pedagogical proposal of the Knowledge Day (JC) of the Luís Eduardo Magalhães State College (CELEM), our field empirical study located in the municipality of Tucano-BA. The research considered the phenomenon of culture as a constituent process and constructed by human beings to understand the relationship between youth culture and education based on the voices, feelings, actions and knowledge of the subjects and their sociocultural contexts. It had as central questions: how is the youth culture in the context of the CELEM JC and what are its contributions to the development of youth protagonism in school? In this sense, the general objective was to understand the configuration of youth culture in the context of the JC of CELEM and its contributions to the development of youth protagonism in school. Four teachers and eleven high school students participated in the research from June to December 2018. The research prioritized a qualitative approach, based on a phenomenological inspiration, ethnographic approach and content analysis. The methodological procedures used to understand the object of research, interpret, construct, analyze official documents (PPP, project and regiment of JC 2018) and the data were obtained through observations recorded in a field journal, photographs, videos and semi-structured interview with teachers and students in daily school activities. The results obtained in this research allow us to conclude that the educational experience of the JC allows the valorization of youth culture and protagonism, the formation of values and the citizenship of students, which are stimulated through artistic and cultural activities during the school year, as well as considered as pillars of the object of study: culture, youth culture, journey, youth and youth protagonism, among other structures of transformation, possible limits for greater effectiveness of the proposal. The study is open to other contributions. Moreover, through empirical research, we hope to have built a relevant work for the CELEM community and for other educational institutions that seek, through cultural practices and educational experiences, to promote learning and citizen training, since human actions build culture(s) and produce their meaning(s)